Folk terminology for Diarrhea in rural Bangladesh - Chowdhury, AMR; Kabir, Zarina N. (Oxford University Press, 2019)
Diarrhea, a descriptive term used in medical science for a variety of clinical diseases denotes an illness that is categorized differently and known by numerous terms in various cultures. These diversified classifications and terminologies are based on the symptoms of diarrheal disorders their perceived etiology, and their treatment. In Bangladesh, four types of illnesses with names derived from folk terminology have been identified for which the clinical symptoms resemble those of diarrhea. These include dud haga, which is due to ingestion of breast milk by infants; ajirno, which is due to overeating; amasha, a mucoid diarrhea; and daeria, which is severe watery diarrhea or cholera. Use of the word diarrhea in epidemiologic evaluations was discovered to be problematic; people confused this term with daeria, which accounted for only 5% of all episodes of diarrhea. The implications of such epidemiologic information for a large-scale program of oral rehydration therapy are also discussed.